Merancang Pendampingan Masyarakat Untuk Mencapai Desa Mandiri Dan Berkelanjutan - Firdasari; Zainal Abidin; Ktut Murniati; Dwi Haryono (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2026)
Community assistance is an effective strategy in realizing independent and sustainable villages. Pasuruan Village has great potential in terms of natural and human resources. However, these resources have not been utilized professionally, so assistance is needed. The objective of this community service activity entitled “Designing community assistance to achieve sustainable independent villages” is to build community capacity to analyze village conditions, encourage community initiatives and decision-making, strengthen institutions and social networks in the community, and achieve sustainability after the assistance program ends. The community service activity was carried out using extension and FGD methods. The output of this community service is a final report on community service, which will be published in the Unila Faculty of Agriculture Community Service Journal in 2026.